(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Millions of people in the world suffer from Overactive bladder (OAB). It is characterized by urinary incontinence, increased frequency, and nocturia, which leads to a compromise in the quality of the patient’s life. Traditional treatments comprised of antimuscarinic agents have limitations due to the side effects and reduced long-term effectiveness which creates a demand for alternative therapies. Treatment strategy for overactive bladder (OAB) has changed from antimuscarinics to β3-adrenergic receptor agonists after the discovery of mirabegron in 2012. This review examines the effectiveness of mirabegron in OAB patients and its integration into clinical practice. New advances in disease management mostly depend on the appropriate use of clinical data in guidelines for clarity. This is evident in OAB management with Mirabegron. The landscape has changed, providing new options for healthcare professionals. This review discusses the latest data on mirabegron use, efficacy, safety, cost-effectiveness, and its potential use in combination therapies. In addition to its position in OAB management, the futuristic use of this β3-adrenergic receptor agonist will also be explored.